THE LEXICOGRAPHIC REPRESENTATION OF LINGUOCULTURAL UNITS IN UZBEK–ENGLISH LEARNER’S DICTIONARIES: SEMANTIC, CULTURAL, AND PRAGMATIC PERSPECTIVES - Nashirova Shaxnoza Buriyevna (Prospects for innovative technologies in science and education, 2026)
Linguocultural units such as idioms, figurative expressions, and culture-bound phrases constitute a crucial component of communicative competence in foreign language learning. In Uzbek–English learner’s dictionaries, these units present considerable challenges due to semantic opacity, cultural specificity, and pragmatic complexity. This article investigates the representation of linguocultural units in Uzbek–English educational dictionaries, focusing on idiomatic expressions and figurative language. The study analyzes lexicographic strategies, identifies recurrent shortcomings, and draws on empirical data from dictionary analysis and learner-oriented studies. Statistical findings indicate that a significant proportion of linguocultural units are inadequately explained, which limits learners’ semantic and pragmatic comprehension. The paper proposes methodologically grounded recommendations for improving the lexicographic treatment of linguocultural units in bilingual learner’s dictionaries.